Forms of interaction of units of the National Police units with the public under martial law - O. M. Muzychuk; A. T. Komziuk; V. O. Naida (Bulletin of Kharkiv National University of Internal Affairs)
The team of authors has emphasised that the issue of forms of interaction between the police and the public under martial law is becoming one of the basic ones, the study of which is of a strategic nature, as it is related to the establishment of stable mutual relations between the police and the public at the organisational, managerial and ideological levels, which in the future can contribute to mutual coverage and complementation of problematic aspects of the activities of both police units and the public. In the course of the research, the authors’ understanding of the public under martial law has been formed, taking into account the international and virtual dimensions of its functioning, as well as the main features of its activity have been highlighted. An attempt has also been made to outline the features of police activity under martial law, which in one way or another are related to interaction with the public. Also, the most common forms of interaction between the police and the public were separately considered: joint delivery of humanitarian aid to the civilian population and units of the Armed Forces of Ukraine, the escort by the police of humanitarian cargo organized by the public; joint evacuation of the population from the regions of active hostilities, ensuring public safety at all stages of evacuation; joint trainings for the public on safety issues, provision of police premises, including shelter, for public safety needs; the use of police premises as “points of invincibility”, allowing the public to use generators, heaters, etc.; conducting trainings by the representatives of the public for the personnel of police units, in particular, participation in the organization of trainings on pre-medical care of representatives of public organizations, paramedics and professional trainers on pre-medical care.